Dimensions of Systemic Failure in Traditional Market Waste Management: A Scoping Review of Empirical Studies in Bandung Raya Metropolitan Area - Tri Widarmanti; Agus Rahayu; Lili Adi Wibowo; Nurul Aziz Pratiwi (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
This study examines the persistent challenges of waste management in traditional markets within the Bandung Raya metropolitan area, Indonesia. Traditional markets contribute significantly to urban waste generation, particularly organic waste, which creates environmental, health, and governance concerns. The study aims to analyze the dimensions of systemic failure in traditional market waste management by synthesizing empirical findings from previous studies conducted across various market locations in Bandung Raya. This research employed a scoping review design following the PRISMA-ScR framework. Data were collected from Google Scholar, Garuda, SINTA, and Scopus databases, resulting in twelve empirical studies published between 2014 and 2025 that met the inclusion criteria. Thematic synthesis was used to identify recurring patterns and dimensions of failure across the studies. The findings reveal five interconnected dimensions of systemic failure: technical-operational gaps, behavior-awareness gaps, participation-incentive gaps, governance-coordination gaps, and institutional-regulatory gaps. Inadequate infrastructure, weak stakeholder coordination, low waste-sorting participation, and limited policy implementation were consistently identified across market locations. The study also highlights the potential of a circular economy model to transform waste management from a financial burden into an economic opportunity, particularly through organic waste processing. In conclusion, improving traditional market waste management requires integrated interventions addressing all five systemic dimensions simultaneously. The study provides an evidence-based foundation for future policy development and research on sustainable urban waste governance.